Diagnostic value of standardized assays for anti-neutrophil cytoplasmic antibodies in idiopathic systemic vasculitis - Hagen, E. Christiaan; Daha, Mohamed R.; Hermans, Joseph M. H.; Andrassy, Konrad; Csernok, Elena; Gaskin, Gillian; Lesavre, Phillippe; Lüdemann, Jens; Rasmussen, Niels; Sinico, R. Alberto; Wiik, Allan; Woude, Fokko J. van der (Kidney international, 1998)
Diagnostic value of standardized assays for anti-neutrophil cytoplasmic antibodies in idiopathic systemic vasculitis. Anti-neutrophil cytoplasmic antibodies (ANCA) are widely used as diagnostic markers for Wegener’s granulomatosis (WG), microscopic polyangiitis (MPA), Churg-Strauss syndrome (CSS) and idiopathic rapidly progressive glomerulonephritis (iRPGN). The objective of this study was to evaluate the diagnostic value of ANCA measurement by the indirect immunofluorescence (IIF) test, and by anti-PR3 and anti-MPO ELISA performed in different locations, in patients with idiopathic small vessel vasculitis. Fourteen centers participated in a standardization study of ANCA assays, and entered a total number of 169 newly diagnosed and 189 historical patients with idiopathic systemic vasculitis or iRPGN. Patients were classified according to a pre-defined diagnostic classification system. Results were compared with those of 184 disease controls and 740 healthy controls. The IIF test was performed according to standard methodology; ELISAs had been standardized among the participants in a previous phase of the study. The sensitivities of assays in patients were as follows. The sensitivity in WG was: cANCA 64%, pANCA 21%, anti-PR3 66%, anti-MPO 24%. In MPA the sensitivity was: cANCA 23%, pANCA 58%, anti-PR3 26%, anti-MPO 58%. Sensitivity in iRPGN was: cANCA 36%, pANCA 45%, anti-PR3 50%, anti-MPO 64%. The specificity of assays (related to disease controls) was: cANCA 95%, pANCA 81%, anti-PR3 87%, anti-MPO 91%. When the results of the IIF test were combined with those of the ELISAs (cANCA/anti-PR3 positive, pANCA/anti-MPO positive), the diagnostic specificity increased to 99%. The sensitivity of the combination of cANCA + anti-PR3 or pANCA + anti-MPO for WG, MPA or iRPGN was 73%, 67% and 82%, respectively. From this study we conclude that the value of the IIF test for ANCA detection can be greatly increased by the addition of a well standardized antigen-specific ELISA. In a significant number of patients with idiopathic small vessel vasculitis, however, the ANCA test results (either in IIF or ELISA) are negative.
Online veröffentlicht am 1. März 1998, Artikelversion 16. Dezember 2015
Gesehen am 26.09.2023